A discussion on the 'dispensable' amino acids. Issue 5 (September 2021) - Ennis, Madeleine A.; Elango, Rajavel
Abstract : Purpose of review: Recently, the concept of dietary dispensable amino acids has been increasingly challenged, as more indirect and direct (experimental) evidence has pointed to the need for them in the diet during specific life stages or disease states. Here, we discuss the classification of amino acids, methods to assess the needs for dispensable amino acids with experimental evidence from our recent studies, and highlight the role of specific dispensable amino acids in metabolism and health. Recent findings: There exist differences among the dispensable amino acids to act as effective nitrogen sources in humans. Glycine, a dispensable amino acid is conditionally indispensable in later stages of human pregnancy. Summary: The so-called 'dispensable' amino acids are quantitatively nearly 75% of the daily protein needs in humans. In certain life-stages and diseases, there is a dietary demand for the dispensable amino acids. Future well-designed studies are required to identify the dietary demand for these amino acids, which will certainly be useful for dietary management in specific diseases and to maintain health across all life-stages.